2016
DOI: 10.1080/17843286.2016.1196862
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fatigue syndrome – an update

Abstract: Despite extensive research, none of the proposed etiological factors have shown strong, reproducible scientific evidence. Over the years, the biopsychosocial model integrating many of the proposed hypotheses has been gaining popularity over the biomedical model, where the focus is on one physical cause. Since the etiological mechanism underlying chronic fatigue syndrome is currently unknown, disease-specific treatments do not exist. Various treatments have been investigated but only cognitive behavior therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 80 publications
1
13
0
3
Order By: Relevance
“…Our results on case characteristics are in line with several other studies on specific FSS It is a consistent finding that the female sex dominates in both IBS [10][11][12][13]49 , FM 5,14,16,50 , CFS 17,19,51 , WAD 52 , and MCS 22,23 . However, one study did not find any pronounced predominance of the female sex in FM 53 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results on case characteristics are in line with several other studies on specific FSS It is a consistent finding that the female sex dominates in both IBS [10][11][12][13]49 , FM 5,14,16,50 , CFS 17,19,51 , WAD 52 , and MCS 22,23 . However, one study did not find any pronounced predominance of the female sex in FM 53 .…”
Section: Discussionsupporting
confidence: 92%
“…Unemployment and the inability to maintain a job have also previously shown to be associated with both IBS 10,11 , FM 16,50 , and CFS 17,51 .…”
Section: Discussionmentioning
confidence: 95%
“…In this report, of the 54 ME/CFS patients, 50% received financial disability compensation. Low employment rates are believed to contribute to the economic burden imposed by ME/CFS [23]. Using archival data from USA, Jason and colleagues reported that the annual direct cost per ME/CFS patient was estimated between US$2,342 and US$8,675 [24].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on how best to treat either ES [9] or CFS [10]. In both conditions, cognitive behavioural therapy (CBT) and multidisciplinary rehabilitation are the usual treatment approaches [9,[11][12][13][14]. In a randomized control trial for ES comparing Qigong alone (gentle movements, body awareness, balance and coordination, breathing, relaxation and mindfulness) or in combination with CBT, 75% of patients in both treatment arms had returned to work at the three-year follow-up [15].…”
Section: Precipitating Factormentioning
confidence: 99%